Efficient urine removal, simultaneous elimination of emerging contaminants, and control of toxic chlorate in a photoelectrocatalytic-chlorine system. (December 2020) - Fang, Fei; Zhang, Yan; Bai, Jing; Li, Jinhua; Mei, Xiaojie; Zhou, Changhui; Zhou, Mengyang; Zhou, Baoxue
Abstract: Urine, which is an important waste biomass resource, is the main source of nitrogen in sewage and contains large quantities of emerging contaminants (ECs). In this study, we propose a new method to efficiently remove urine, simultaneously eliminate ECs, and control the generation of toxic chlorate during urine treatment using a photoelectrocatalytic-chlorine (PEC-Cl) system. A type-II heterojunction of WO3 /BiVO4 was used as a photoanode to generate chlorine radicals (Cl) by decreasing the oxidation potential of WO3 valence band for the highly selective conversion of urine to N2 and the simultaneous degradation of ECs in an efficient manner. The method presented surprising results. It was observed that the amount of toxic chlorate was significantly inhibited by circumventing the over-oxidation of Cl − by holes or hydroxyl radicals (OH). Moreover, the removal of urea nitrogen reached 97% within 90 min, while the degradation rate of trimethoprim in urine was above 98.6% within 60 min, which was eight times more than that in the PEC system (12.1%). Compared to the bare WO3 photoanode, the toxic chlorate and nitrate generated by the WO3 /BiVO4 heterojunction photoanode decreased by 61% and 44%, respectively. Thus, this study provides a safe, efficient, and environmentally-friendly approach for the disposal of urine. Graphical abstract: Image 1 Highlights: Highly selective conversion of urine to N2 was obtained by using a PEC-Cl system. Emerging contaminants in urine were efficiently removed simultaneously. Toxic chlorate was also inhibited in the system with the WO3 /BiVO4 photoanode. Abstract : we proposed a WO3 /BiVO4 heterojunction photoanode based on the PEC-Cl system for urine removal as well as the simultaneous elimination of ECs and control of toxic chlorate.